Characterization of Myxovirus resistance protein in birds showing different susceptibilities to highly pathogenic influenza virus - HAGIWARA, Katsuro; NAKAYA, Takaaki; ONUMA, Manabu (Journal of Veterinary Medical Science, 2020)
We compared the Mx expression and anti-viral function and the 3D structure of Mx protein in four species: chicken (Gallus gallus), whooper swan (Cygnus cygnus), jungle crow (Corvus macrorhynchos), and rock dove (Columba livia). We observed different mortalities associated with highly pathogenic avian influenza virus (HPAIV) infection to understand the relationship between Mx function as an immune response factor and HPAIV proliferation in bird cells. Different levels of Mx were observed among the different bird species after virus infection. Strong Mx expression was confirmed in the rock dove and whooper swan 6 hr after viral infection. The lowest virus copy numbers were observed in rock dove. The virus infectivity was significantly reduced in the BALB/3T3 cells expressing rock dove and jungle crow Mx. These results suggested that high Mx expression and significant Mx-induced anti-viral effects might result in the rock dove primary cells having the lowest virus copy number. Comparison of the expected 3D structure of Mx protein in all four bird species demonstrated that the structure of loop L4 varied among the investigated species. It was reported that differences in amino acid sequence in loop L4 affect antiviral activity in human and mouse cells, and a significant anti-viral effect was observed in the rock dove Mx. Thus, the amino acid sequence of loop L4 in rock dove might represent relatively high anti-viral activity.